Componentes voláteis de espécies de burseraceae - (:unkn) unknown (Museu Paraense Emílio Goeldi, 1999)
The Burseraceae family is distributed in tropical and subtropical regions, mainly in northeastern Africa, Arabia, and tropical America. Its species characteristically exude oil-resins and gum-resins, which have medicinal and industrial properties. Among the 21 genera in this family, Protium is the most abundant in Tropical America, especially in the Amazon region. In the essential oils of Burseraceae species, osmonones and sesquiterpenes predominate. In this work the results obtained about the chemical composition of the essential oils of the species P. heptaphyllum and Protium cf. apiculatum are presented. The oils were obtained by microhydrodistillation, in a 3h interval, from material dried at room temperature for 7 days. The chemical composition of the oils was obtained by gas chromatography-mass spectrometry, in a Finnigan lNCOS-XL CGIEM system, equipped with a DB-5 fused silica capillary column, temperature program, 60°C-240°C (3°C/min) and helium as carrier gas. The main = components identified in the oil obtained from the leaves of P. heptaphyllum were trans-caryophyllene (22.2%), germacrene D (20.4%) and bicyclogermacrene (14.8%); in the oil obtained from the bark the main components identified were N 4-terpineol (17.2%) and a-gurjunene (10.0%). The oil obtained from Protium cf. apiculatum did not show a majority constituent, but a mixture of 38 components, in levels below 10.0%.
Volatile components of burseraceae species
Keywords: Burseraceae; Protium; Óleos essenciais; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA